2016
DOI: 10.1177/0271121416662870
|View full text |Cite
|
Sign up to set email alerts
|

Examining Paraprofessional Interventions to Increase Social Communication for Young Children With ASD

Abstract: Interventions and Autism Spectrum Disorder Social communication skill development begins early in infancy and continues throughout childhood. During the first year of life, a child learns to deliberately communicate through social exchanges such as smiling, coordinating attention between objects and people, and using sound and gestures (Wetherby, 2006). Such early social engagement lays the foundation for more complex social interactions that emerge in early childhood, including imitation, imaginary play, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 49 publications
(250 reference statements)
0
15
0
1
Order By: Relevance
“…Studies published before 1979 conceptualized paraprofessionals as aides working in a hospital setting, counseling center, and so forth. Initially, seven published reviews were identified that included paraprofessionals, however the reviews included studies of paraprofessionals among multiple types of intervention providers and/or were limited primarily to the provision of supports for students with disabilities (i.e., Brock & Carter, 2013, 2017; Douglas, 2012; Garrote et al, 2017; Mrachko & Kaczmarek, 2017; Rispoli et al, 2011; Walker & Smith, 2015). These seven reviews and the studies found in the aforementioned databases and peer‐reviewed journals yielded a total of 108 articles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies published before 1979 conceptualized paraprofessionals as aides working in a hospital setting, counseling center, and so forth. Initially, seven published reviews were identified that included paraprofessionals, however the reviews included studies of paraprofessionals among multiple types of intervention providers and/or were limited primarily to the provision of supports for students with disabilities (i.e., Brock & Carter, 2013, 2017; Douglas, 2012; Garrote et al, 2017; Mrachko & Kaczmarek, 2017; Rispoli et al, 2011; Walker & Smith, 2015). These seven reviews and the studies found in the aforementioned databases and peer‐reviewed journals yielded a total of 108 articles.…”
Section: Methodsmentioning
confidence: 99%
“…Given the gap in paraprofessional training, a comprehensive appraisal of the extant PD literature is urgently needed. To date, existing reviews have included paraprofessionals among multiple types of intervention providers or have been limited to only support for students with severe intellectual or developmental disabilities (e.g., Brock & Carter, 2013, 2017; Douglas, 2012; Garrote, Dessemontet, & Opitz, 2017; Mrachko & Kaczmarek, 2017; Rispoli, Neely, Lang, & Ganz, 2011; Walker & Smith, 2015). Specifically seven reviews have included studies investigating training and supports for paraprofessionals in providing services to students with severe intellectual or developmental disorders or a broad range of disabilities, including core competencies and interventions and supports needed to meet the unique learning and social behavior needs of the students.…”
Section: Introductionmentioning
confidence: 99%
“…Search terms indicating NDBIs (e.g., Incidental Teaching and Pivotal Response Training) were based on those listed in the works of Schreibman and colleagues (2015). Immediately following the initial electronic search, ancestral searches of reference lists were conducted from related systematic reviews (i.e., Lane et al, 2016; Mrachko & Kaczmarek, 2017; Snyder et al, 2015; Verschuur et al, 2014). See Figure 1 for a PRISMA flowchart (Moher, Liberati, Tetzlaff, & Altman, 2009) outlining the specific systematic review sequence, number of studies located, and exclusions.…”
Section: Methodsmentioning
confidence: 99%
“…Previous systematic reviews have established many caregiver and practitioner-implemented NDBIs as effective, evidence-based practices for young children with disabilities (e.g., Lane, Lieberman-Betz, & Gast, 2016; Lang, Machalicek, Rispoli, & Regester, 2009; Mrachko & Kaczmarek, 2017; Rispoli, Neely, Lang, & Ganz, 2011; Snyder et al, 2015; Verschuur, Didden, Lang, Sigafoos, & Huskens, 2014). Yet, these reviews pay little attention to the assessment of social validity.…”
Section: Practitioner-implemented Ndbismentioning
confidence: 99%
See 1 more Smart Citation